The Herd Health Handbook for Goat Producers: Control of Parasites in Goats - Ray Mobley; Carmen Lyttle-N’guessan; Thomas Peterson (EDIS, 2009)
FAMU003, a 3-page illustrated fact sheet by Ray Mobley, Carmen Lyttle-N'guessan, and Thomas Peterson, describes the effects of external and internal parasites on goat health and production, common internal parasites in Florida (coccidia and helminthes), and preventative measures in controlling internal parasites infestation, including the FAMACHA© System. Includes references. Published by the Florida A & M University Extension, September 2009.